Cluster analysis on breath print of newly diagnosed COPD patients: effects of therapy. (8th June 2018) - Scarlata, Simone; Finamore, Panaiotis; Santangelo, Simona; Giannunzio, Gilda; Pennazza, Giorgio; Grasso, Simone; Santonico, Marco; Incalzi, Raffaele Antonelli
Abstract: Background: Chronic obstructive pulmonary disease (COPD) is a highly heterogeneous disease and airflow limitation and symptoms only partially capture such heterogeneity. Since COPD is known to affect the production of volatile organic compounds (VOCs), we aimed to verify to which extent exhaled VOCs can characterize newly diagnosed COPD patients and changes in response to inhaled therapy. Materials and methods: Fifty newly diagnosed COPD patients were consecutively recruited among those attending the pulmonary medicine outpatient clinic at 'Campus Bio-Medico' University Hospital. VOCs were collected using the Pneumopipe ® and analysed by the BIONOTE electronic nose both at baseline and after 12 weeks of inhaled therapy. Patients were grouped using K-mean cluster analysis on BIONOTE responses and the obtained clusters were compared via non-parametric tests. Results: We identified three clusters of subjects: (a) without remarkable comorbidities; (b) with air trapping and higher BODE index score (mean 1.2); (c) without air trapping and with a lower BODE index. Inhaled bronchodilators caused a quantitative reduction in the amound of VOCs, while inhaled steroids provided a qualitative modification of the breath profile. Conclusion: VOCs patterns categorize newly diagnosed COPD subjects. VOCs production declines after bronchodilators administration and changes in quality after topic steroid treatment.